Evaluation of the Ovarian Reserve in Women With Systemic Lupus Erythematosus - Felipe Arturo Morales-Martínez; Celina Salas-Castro; Manuel Rolando García-Garza; Otto Valdés-Martínez; Selene Marysol García-Luna; Mario Garza-Elizondo; Oscar Vidal-Gutiérrez; Donato Saldívar-Rodríguez; Luis Humberto Sordia-Hernández (Tehran University of Medical Sciences, 2021)
Objective: Systemic lupus erythematosus (SLE) is a chronic multisystem autoimmune disorder where the disease activity itself and the medications used for its treatment, may have adverse effects on ovarian function. This study aimed to assess the ovarian reserve (OR) in SLE patients. Materials and methods: The anti-müllerian hormone (AMH) and the antral follicle count (AFC), two markers to evaluate the OR was assessed in 64 SLE patients and compared to normal individuals. Additionally, we assessed whether the disease per se or the pharmacological treatments affect the OR. Results: Patients with SLE displayed alterations in the OR regardless of the presence of alterations of the menstrual cycle. The AFC and AMH were significantly lower in SLE patients with and without menstrual alterations when compared to control individuals (p<0.0001). However, the AFC and AMH levels were significantly correlated (p=0.006) in the SLE patients with menstrual alterations. Except for hydroxychloroquine that was statistically higher in SLE patients with menstrual alterations (p=0.04), the cumulative dose for cyclophosphamide, corticosteroid, and methotrexate was similar in SLE patients regardless of the occurrence of menstrual alterations. Conclusion: The monitoring of AMH and AFC in SLE patients should be used to detect the rapid and irreversible decline of the OR to provide a possibility of pregnancy to the SLE patients.